Influence of Intrinsic Trapping on The Performance Characteristics of ZnO-Bi2O3 Based Varistors - Mohammad A. Alim (Active and Passive Electronic Components)
The lumped parameter/complex plane analysis technique reveals several contributions to the ac small-signal terminal immittance of the ZnO-Bi2O3 based varistors' grain-boundary response. The terminal capacitance constitutes multiple trapping phenomena, a barrier layer contribution, and a resonance effect in the frequency range 10-2 ≤ f ≤ 109 Hz. A trapping response near to ∼105 Hz (∼10-6 s), observed via the loss-peak and a distinct depressed semicircular relaxation in the complex capacitance plane, is common to all well-formed (exhibiting good performance for applications) devices regardless of the composition recipe and processing route. This trapping is attributed to possible formation of ionized intrinsic or native defects, and believed to be predominant within the electric field falling regions across the microstructural grain-boundary electrical barriers. The nature of rapidity of this intrinsic trapping and the corresponding degree of uniformity/non-uniformity can be utilized in conjunction with relevant information on other competing trapping phenomena to assess an overall performance of these devices. The constituting elements, responsible for the average relaxation time of the intrinsic trapping, indicate some sort of possible surge arrester (i.e., suppressor/absorber) applications criteria in the power systems' protection. The factors related to materials' history, composition recipe, and processing variables influence or modify relative magnitudes and increase or decrease the visibility of the constituting elements without distorting devices' generic dielectric behavior.